Germination, Vigor and Seedling Growth of Soybean after Seed Coating and Pelleting with Bacillus subtilis - Kangsopa, Jakkrapong; Jeephet , Phetcarat; Chantain, Sureemard (Recent Science and Technology, 2022)
Soybeans are an important economic crop in Thailand. However, the soybean seeds used for growing soybeans lack quality and standards. This results in inconsistent and weak seedlings after cultivation, which can be easily destroyed by diseases and pesticides. This current experiment aims to study the effect of seed coating and seed pelleting using Bacillus subtilis on the germination, vigor, and growth of soybean seedlings. The experiment was conducted at the Seed Technology Laboratory, Agronomy Major, Faculty of Agricultural Production, Maejo University. An experimental design was done in a completely randomized design (CRD). The results of the experiment were as follows. Seeds coated with 0.5 milliliters of B. subtilis had the highest rate of radicle emergence at 99 %. Moreover, the speed of radicle emergence and speed of germination were statistically significantly higher compared to untreated seeds. On the other hand, all seeds coated with the B. subtilis and normal coated treatments gave the best germination rate. In addition, seeds coated with 0.5 milliliters of B. subtilis still had higher shoot length, root length, and total seedling quality when compared with untreated seeds under laboratory conditions. Under greenhouse conditions, compared to seed coating and pelleting, seed coating in combination with B. subtilis gave the best germination. Therefore, seed coating with 0.5 milliliters of B. subtilis is the most suitable method and recommended rate for soybean seed enhancement.